The Challenges of Prophetic Digital Public Relations in the Disruptive Era - Muhammad Iqbal Apriliansyah; Mutia Naya Oktaviani; Nazwa Aura Kamal; Novita Dwi Yanti (Pen of Social Science, 2026)
This study examines how prophetic values are integrated into digital Public Relations (PR) practices and identifies the challenges of their implementation in the disruptive era. Using a Systematic Literature Review (SLR) with the PRISMA framework, this study analyzes selected scholarly articles published between 2018 and 2025 from indexed national and international journals. The selection process involved keyword-based searches, screening, eligibility assessment, and thematic coding of relevant studies. The findings indicate three main patterns. First, prophetic values are operationalized through ethical storytelling, transparent communication, and socially responsible content strategies. Second, the implementation of these values faces structural, cultural, and technological challenges, including algorithmic bias, market-driven communication logic, and institutional constraints. Third, prophetic digital PR contributes to building trust and fostering more sustainable and human-centered communication, although its application remains limited and context-dependent. This study contributes theoretically by bridging classical PR models, particularly two-way symmetrical communication, with prophetic ethics, and empirically by mapping current research trends and gaps in value-based digital communication.